Quantum Integral Inequalities on Finite Intervals - Taher, Farhad Mustafa (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2018)
The Integral Inequalities can be used for the study of qualitative and quantitative properties of integrals and they perform an important role in the theory of differential equations. The study of the fractional q-integral inequalities is also of great importance. The purpose of this thesis is to study q-calculus analogs of some classical integral inequalities. In particular, some of the greatest significant integral inequalities of analysis are extended to Quantum calculus. We will work on the q-generalization of the Hölder, Hermite-Hadamard, Trapezoid, Ostrowski, Cauchy-BunyakovskySchwarz, Grüss, and Grüss-Chebysev integral inequalities. The analysis is based on the notions of q-derivative and q-integral on finite intervals presented recently by the author in [9]. Keywords: Quantum Integral Inequalities; Hölder’s inequality, Hermite-Hadamard’s inequality, Ostrowski's Inequality, Grüss-Chebysev integral inequality

ÖZ: İntegral eşitsizlikleri, integrallerin nitel ve nicel özelliklerinin incelenmesi için kullanılabilir ve diferansiyel denklemler teorisinde temel bir rol oynar. Kesirli qintegral eşitsizliklerinin incelenmesi de büyük önem taşımaktadır. Bu çalışmanın amacı bazı klasik integral eşitsizliklerinin q-Kalkülüs analoglarını bulmaktır. Özellikle analizin en önemli integral eşitsizliklerinin bazılarının kuantum Kalkülüs’e genelleştirmelerini incelenecektir. Bunlar, Hölder, Hermite-Hadamard, Trapezoid, Ostrowski, Cauchy-Bunyakovsky-Schwarz, Grüss ve Grüss-Čebyšev integral eşitsizlikleri olacaktır. Yapılan çalışmalar ve analizler, son zamanlarda J. Tariboon ve S. Ntouyas v.s. araştırmacıların çalıştığı sınırlı aralıklarda q-türev ve qintegral kavramlarına dayanmaktadır. Anahtar Kelimeler: Quantum İntegral eşitsizlikleri, Hölder eşitsizliği, HermiteHadamard eşitsizliği, Ostrovski eşitsizliği, Grüss-Chebysev eşitsizliği, Konvekslik
Master of Science in Mathematics. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Arts and Sciences, Dept. of Mathematics, 2018. Supervisor: Prof. Dr. Sonuç Zorlu Oğurlu.
Keywords: Differential equations--Numerical solutions; Quantum Integral Inequalities; Hölder’s inequality; Hermite-Hadamard’s inequality; Ostrowski's Inequality; Grüss-Chebysev integral inequality; Mathematics